Glycyrol targets Pneumolysin (PLY) oligomerization to reduce Streptococcus pneumoniae toxicity - Li, Yudi; Wu, Hongji; Hu, Yibo; Meng, Haoji; Xu, Yan (Frontiers in Pharmacology, 2024)
Aim of the study:Exploring the potential of glycyrol to reduce the invasiveness of Streptococcus pneumoniae（S. pneumoniae）. Materials and methods: Cell experiments were performed using A549 alveolar epithelial cells and S. pneumoniae D39. Glycyrol was added to A549 cells mixed with or without Pneumolysin（PLY） to detect the effect of Glycyrol on PLY toxicity. Glycyrol was used to detect the effect on S. pneumoniae toxicity and PLY production. Mice was used to detect the anti-infectious ability of Glycyrol to regulate S. pneumoniae infection. Western blot and Molecular docking were used to detect how and where Glycyrol inhibits PLY toxicity. Results: we discovered that glycyrol, a main component of the widely recognized Chinese herbal medicine licorice, reduce the virulence of PLY in S. pneumoniae invasion; glycyrol achieves this effect by interacting with PLY through hydrogen bonding, van der Waals interactions, and solvation effects to reduce the pore-forming toxicity of PLY. Moreover, glycyrol did not affect the growth of S. pneumoniae or the production of PLY. Conclusion: We have actually discovered that Glycyrol, a major component of the widely known Chinese herbal medicine Glycyrrhiza uralensis Fisch., interacts with PLY through hydrogen bonds, Van der Waals and solvation to reduce the pore-forming toxicity of PLY and the toxicity of S. pneumoniae invasion, while not affecting the growth of S. pneumoniae and the production of PLY.